Biological synthesis of Zinc Nanoparticles by fungus species - Ariffin, Ainnur Farhana; Ibrahim Ali , Noorbatcha; Mohd. Salleh, Hamzah (2013)
Nanoparticles have gained interest due to its unique properties and benefits that can upgrade the future technologies. However, the production of nanoparticles has adopted physical and chemical methods which have been proven as non-eco friendly and produces toxic products. The present study proposes an eco-friendly synthesis of zinc nanoparticles using a wide range of microorganisms from varies of bacteria species to the uses of fungi species. The synthesis of zinc nanoparticles using Aspergillus niger is presented in this paper. It’s also include the studies of the effect of biomass concentration when challenged to the salt solution and effect of different type of salt solution used to be challenged with the fungal mycelia. The fungus is grown in a suitable medium and mycelia biomass was taken (varies in the concentration) to be challenged with the zinc sulphate salt solutions and zinc nitrate salt solution (at different concentration) for 72 hours. Stability studies were done by further the incubation period up to more than 72 hours. The formations of nanoparticles were characterized using UV–Vis spectrophotometer and Scanning Electron Microscope (SEM) to ascertain the size and polydispersity of the nanoparticles produced. The lower concentration of biomass used in the synthesis yield more nanoparticles formation.